Method for manufacturing molded body for sheet electrode
By using electrode materials with high concentration solid components and a vibrating scraper of specific shapes, the problem of thickness deviation of electrode materials is solved, and excellent thickness in-plane uniformity of the sheet electrode molded body is achieved.
Patent Information
- Application Number
- CN202380057124.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-25
- Publication Date
- 2025-03-14
AI Technical Summary
When manufacturing an electrode molded body for semi-solid state batteries or all-solid state batteries, if an electrode material that does not contain an electrolyte or a small electrolyte is used, the thickness of the electrode material film will be deviated, making it difficult to obtain a sheet-shaped electrode molded body with excellent in-plane uniformity of thickness.
An electrode material film is formed on the support body using an electrode material containing an electrode active material and a solid component concentration of 30 volume % or more. By using a scraper having a shape that protrudes from both ends in the width direction and vibrates, it moves relatively along the support surface, and limits the thickness and width of the electrode material to ensure in-plane uniformity.
The sheet-shaped electrode molded body with excellent in-plane uniformity of thickness is achieved, and the problem of thickness deviation of electrode material film is avoided.
Smart Images

Figure CN119631192A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a formed body for a sheet-like electrode. Background Art
[0002] In recent years, research on the development of semi-solid-state batteries or all-solid-state batteries is underway.
[0003] The production of electrodes for use in semi-solid batteries or all-solid batteries includes, for example, a step of coating an electrode material including an electrode active material in the form of powder on a support.
[0004] For example, Japanese Patent Gazette No. 2017-533548 discloses a method for manufacturing an electrochemical cell, which includes a step of coating a semi-solid anode on the first surface of a negative current collector, and the step includes the following steps: configuring a frame that defines an opening on the first surface of the negative current collector; configuring a semi-solid anode in the opening of the frame; and removing excess semi-solid anode material from the opening, and also discloses using a vibrating scraper to remove excess semi-solid anode material.
[0005] Furthermore, as a method for applying a material containing a powder regardless of the manufacture of an electrode, for example, Japanese Patent Gazette No. 2011-071153 discloses a method in which a metal paste containing a metal powder having an average particle size of 0.005 μm to 1.0 μm and an organic solvent is used, and the metal paste is applied to a substrate while mechanical vibration at a frequency of 60 Hz to 100 kHz is applied to the metal paste. Summary of the invention
[0006] Technical issues to be solved by the invention
[0007] When manufacturing an electrode molded body for a semi-solid battery or an all-solid battery, a process is included in which an electrode material containing an electrode active material is used to form an electrode material film having a thickness corresponding to the sheet-shaped electrode molded body. In this process, if an electrode material containing no electrolyte or a small amount of electrolyte is used, the thickness of the electrode material film will vary, making it difficult to obtain a sheet-shaped electrode molded body with excellent in-plane uniformity of thickness.
[0008] Therefore, the present invention has been completed in view of the above circumstances.
[0009] An object of one embodiment of the present invention is to provide a method for producing a sheet-like electrode molded body having excellent in-plane uniformity of thickness.
[0010] Means for solving technical problems
[0011] The present invention includes the following aspects.
[0012] <1> A method for producing a sheet-shaped electrode molded body, comprising the step of forming an electrode material film on a support using an electrode material containing an electrode active material and having a solid content concentration of 30% by volume or more,
[0013] The electrode material film is formed in the following manner: a scraper having a shape in which both ends in the width direction protrude more than the central part in the width direction and in which the central part in the width direction vibrates is moved relative to the surface of a support body while maintaining a constant distance from the surface of the support body; the thickness of the electrode material supplied to the support body is limited by the gap between the surface of the support body and the central part in the width direction of the scraper, and the width is limited by both ends in the width direction of the scraper which protrude more than the central part in the width direction.
[0014] <2> The method for producing a sheet-shaped electrode molded body according to <1>, wherein:
[0015] At least a portion of the electrode material supplied onto the support and before the thickness and width of the electrode material are restricted forms a reservoir in a region sandwiched between the support and the squeegee.
[0016] <3> The method for producing a sheet-shaped electrode molded body according to <2>, wherein:
[0017] The electrode material is continuously or intermittently supplied to the reservoir.
[0018] <4> The method for producing a sheet-shaped electrode molded body according to <3>, wherein:
[0019] The ratio X:Y of the amount X of the electrode material supplied to the reservoir and the amount Y of the electrode material film formed on the support is 1:0.1 to 1:1 on a mass basis.
[0020] <5> The method for producing a sheet-like electrode molded body according to any one of <1> to <4>, wherein:
[0021] The friction coefficient μ1 of the contact portion of the scraper contacting the electrode material and the electrode material is smaller than the friction coefficient μ2 of the electrode material and the support.
[0022] <6> The method for producing a sheet-like electrode molded body according to any one of <1> to <5>, wherein:
[0023] The ratio A:B of the amplitude A of the central portion in the width direction of the vibrating scraper and the thickness B of the electrode material film formed on the support is 1:10 to 1:200.
[0024] Effects of the Invention
[0025] According to one embodiment of the present invention, it is possible to provide a method for producing a molded body for an electrode, which can produce a sheet-shaped molded body for an electrode having excellent in-plane uniformity of thickness. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram for explaining an example of an apparatus used in the step of forming an electrode material film in the method for producing a molded body for an electrode according to the present invention.
[0027] Figure 2 This is a schematic diagram for explaining an example of an apparatus used in the step of forming an electrode material film in the method for producing a molded body for an electrode according to the present invention.
[0028] Figure 3 It is a schematic diagram for explaining an example of the shape of the scraper.
[0029] Figure 4 It is a schematic diagram for explaining another example of the shape of the scraper.
[0030] Figure 5 The right side schematic diagram for explaining an example of the shape of the scraper. DETAILED DESCRIPTION
[0031] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. The present invention is not limited to the following embodiments and can be implemented with appropriate changes within the scope of the purpose of the present invention. Constituent elements represented by the same symbols in the drawings refer to the same constituent elements. The description of the constituent elements and symbols repeated in the drawings may sometimes be omitted. The ratio of the dimensions in the drawings does not necessarily represent the ratio of the actual dimensions.
[0032] In the present invention, the numerical range represented by "to" refers to a range including the numerical values recorded before and after "to" as the lower limit and the upper limit. In the numerical range recorded in stages in the present invention, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present invention, the upper limit or lower limit recorded in a certain numerical range can be replaced by the value shown in the embodiment.
[0033] In the present invention, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.
[0034] In the present invention, when a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition refers to the total amount of the plurality of substances present in the composition unless otherwise specified.
[0035] In the present invention, a combination of two or more preferred aspects or configurations is a more preferred aspect or configuration.
[0036] In the present invention, the "solid content" refers to a component that is solid at 25°C and 1 atmosphere, and the "liquid content" refers to a component that is liquid at 25°C and 1 atmosphere.
[0037] In the present invention, the "width direction" of the scraper refers to the direction orthogonal to the direction in which the scraper moves relative to the surface of the support (i.e., the direction in which the electrode material film is formed on the support). That is, the "width direction" of the scraper is also equivalent to the "width direction" of the electrode material film.
[0038] In the present invention, the "central portion in the width direction" of the scraper refers to the central portion in the width direction of the scraper, and is a region determined according to the width of the electrode material film to be formed on the support. In other words, the "end portions in the width direction" of the scraper refers to the two end portions in the width direction of the scraper, and is a region further outward than the "central portion in the width direction".
[0039] <Method for producing a molded body for sheet-shaped electrode>
[0040] The method for manufacturing a sheet electrode forming body involved in the present invention includes a step of forming an electrode material film on a support body using an electrode material containing an electrode active substance and having a solid content concentration of 30 volume % or more, and is formed in the following manner: a scraper having a shape in which both ends in the width direction protrude more than the central part in the width direction and the central part in the width direction vibrates is moved relative to the surface of the support body while maintaining a constant distance from the surface of the support body, and the thickness of the electrode material supplied to the support body is limited by the gap between the support body and the central part in the width direction of the scraper, and the width is limited by both ends in the width direction of the scraper.
[0041] Hereinafter, “the electrode material containing an electrode active material and having a solid content concentration of 30% by volume or more” is also simply referred to as “the electrode material”, and “the sheet-shaped electrode molded body” is also simply referred to as “the electrode molded body”.
[0042] For example, when an electrode material containing an electrode active material and having a solid content concentration of 30% by volume or more is used to form an electrode material film on a support, sometimes the content of the liquid component in the electrode material is not high, and the thickness of the electrode material film varies. As a result, it is difficult to obtain a sheet-shaped electrode molded body with excellent in-plane uniformity of thickness.
[0043] As a result of the research on the above-mentioned subject, the inventors of the present invention have found the following method: when forming an electrode material film on a support using the above-mentioned electrode material, a scraper having a shape in which both ends in the width direction protrude more than the central part in the width direction and the central part in the width direction vibrates is relatively moved along the surface of the support while maintaining a constant distance from the surface of the support, thereby limiting the thickness of the electrode material supplied to the support by the gap between the support and the central part in the width direction of the scraper, and limiting the width by both ends in the width direction of the scraper. According to this method, the electrode material with limited thickness and width is effectively applied to the surface of the support, the thickness of the formed electrode material film is not easy to deviate, and the in-plane uniformity of the thickness of the sheet-shaped electrode molded body is improved.
[0044] As described above, in the method for producing a sheet-like electrode molded body according to the present invention, a sheet-like electrode molded body having excellent in-plane uniformity of thickness is produced.
[0045] [Step of forming an electrode material film]
[0046] The method for producing a molded body for an electrode according to the present invention includes a step of forming an electrode material film on a support using an electrode material.
[0047] In addition, regarding the electrode material film obtained in this process, a scraper having a shape in which both ends in the width direction protrude more than the central part in the width direction and the central part in the width direction vibrates is relatively moved along the surface of the support while maintaining a constant distance from the surface of the support. By the relative movement of the scraper and the support, the thickness of the electrode material supplied to the support can be limited by the gap between the support and the central part in the width direction of the scraper, and the width can be limited by both ends in the width direction of the scraper. As a result, the electrode material with limited thickness and width is applied to the surface of the support, and is formed by the electrode material film on the support.
[0048] In this process, refer to Figure 1 to Figure 5 Provide explanation. Figure 1 and Figure 2 Schematic diagram for explaining an example of an apparatus used in the process of forming an electrode material film. Figure 3 to Figure 5 It is a schematic diagram for explaining the shape of the scraper.
[0049] exist Figure 1 10 indicates a support, 20 indicates a scraper, 30 indicates an electrode material, 32 indicates a storage portion of the electrode material, 40 indicates a pressure shaft for maintaining a constant distance between the scraper and the surface of the support, 50 indicates a cylinder connected to the pressure shaft, 60 indicates a vibrator for vibrating the scraper, and 70 indicates a moving stage for moving the support. The scraper 20 is fixed to a frame not shown.
[0050] Here, reference Figure 3 to Figure 5 , the shape of the scraper 20 will be described.
[0051] like Figure 3 As shown, the scraper 20 has a shape in which both ends 24 in the width direction protrude more than the central portion 22 in the width direction. By setting such a shape, a gap having a distance C is formed between the central portion 22 in the width direction and the surface of the support body 10. At this time, there may be a gap between the both ends 24 in the width direction and the surface of the support body 10, or there may be no gap, but it is preferred that a gap having a distance smaller than the distance C is also formed between the both ends 24 in the width direction and the surface of the support body 10. That is, it is preferred that the both ends 24 in the width direction are in a non-contact state with the surface of the support body 10.
[0052] In the case of the scraper 20, the width of the electrode material film is limited by the inner side surfaces 25 of the two end portions 24 in the width direction, so the width of the formed electrode material film is determined by the width (length) of the central portion 22 in the width direction. From the perspective of forming an electrode material film with a rectangular cross section, as shown in FIG. Figure 3 As shown, it is preferred that the front end surface 23 and the inner side surface 25 of the widthwise central portion 22 are both straight lines, and the angle formed by the front end surface 23 and the side surface 25 is a right angle.
[0053] In addition, if Figure 3 As shown in FIG. 1 , in the scraper 20 , the widthwise central portion 22 and the widthwise end portions 24 are integrated, but the scraper 20 is not limited to this form.
[0054] For example, Figure 4 As shown in the scraper 20A, the scraper body 26A is combined (joined) with the convex parts 28A provided at both ends of the scraper body 26A in the width direction, and a shape in which the two ends 24 in the width direction are more prominent than the central part 22 in the width direction can be formed. In addition, the scraper body 26A and the convex part 28A can be directly combined (joined) or combined (joined) via a joining component. For example, if the joining component is a component that does not transmit or is difficult to transmit vibration, when the scraper body 26A vibrates (it can also be said that the central part 22 in the width direction vibrates), the convex part 28A can be set to a state of not vibrating or slightly vibrating.
[0055] Here, from the perspective of forming an electrode material film having a rectangular cross section, as Figure 4As shown, it is preferred that the front end face 23 of the scraper body 26A (i.e., the front end face 23 of the widthwise central portion 22 of the scraper 20A) and the inner side face 25 of the convex portion 28A (i.e., the inner side face 25 of the widthwise end portions 24 of the scraper 20A) are both straight lines, and the angle formed by the front end face 23 and the side face 25 is a right angle. In addition, as for the convex portion 28A, as long as the side face 25 is a straight line, the angle formed by the front end face 23 and the side face 25 is a right angle, and it does not contact the surface of the support body, there is no particular limitation on the shape and size other than this.
[0056] And, if Figure 5 As shown in the scraper 20B, the scraper body 26B and the width limiting member 28B combined (joined) with the two ends of the scraper body 26B in the width direction can also form a shape in which the two ends 24 in the width direction are more protruding than the central part 22 in the width direction. In addition, the scraper body 26B and the width limiting member 28B can be directly combined (joined) or combined (joined) via a joining member. For example, if the joining member is a member that does not transmit or is difficult to transmit vibration, when the central part 22 in the width direction (that is, the scraper body 26B) vibrates, the width limiting member 28B can be set to a state of not vibrating or slightly vibrating.
[0057] Here, from the perspective of forming an electrode material film having a rectangular cross section, as Figure 5 As shown, it is preferred that the front end face 23 of the scraper body 26B (i.e., the front end face 23 of the width direction center portion 22 of the scraper 20B) and the inner side face 25 of the width limiting member 28B (i.e., the inner side face 25 of the width direction end portions 24 of the scraper 20B) are both straight lines, and the angle formed by the front end face 23 and the side face 25 is a right angle. In addition, as for the width limiting member 28B, as long as the side face 25 is a straight line, the angle formed by the front end face 23 and the side face 25 is a right angle, and it does not contact the surface of the support body, there is no particular limitation on the shape and size other than this.
[0058] In addition, in this process, the relative movement of the scraper and the support body limits the thickness of the electrode material supplied to the support body by the gap between the support body and the central part of the scraper in the width direction, and limits the width by the two ends of the scraper in the width direction. However, the thickness of the electrode material and the width of the electrode material can be limited at the same time, or they can be limited at different times (i.e., with a time difference). For example, when the thickness of the scraper is large, for example, the thickness of the electrode material can be limited after the width of the electrode material is limited, and the thickness of the electrode material and the width of the electrode material can be limited at different times (i.e., with a time difference).
[0059] like Figure 1As shown in the figure, the scraper 20 is provided in such a manner that the central portion 22 in the width direction maintains a constant distance C relative to the surface of the support 10 placed on the moving stage 70. The scraper 20 is connected to the cylinder 50 via the pressure shaft 40, and the scraper 20 is pressed toward the support 10 side in such a manner that the constant distance C is maintained even when the scraper 20 is in contact with the electrode material 30 and the support 10 is moving in the direction of the arrow. In addition, pressure is applied to the scraper 20 in such a manner that the repulsive force (i.e., the force that pushes the scraper 20 away) from the contacted electrode material 30 is opposed, so that the constant distance C is maintained.
[0060] And, if Figure 1 As shown, between the support 10 and the scraper 20, the electrode material 30 supplied to the support 10 is accumulated thicker than the gap having the distance C between the scraper 20 and the support 10, forming an accumulation portion 32. From this state, the support 10 is moved in the direction of the arrow by moving the stage 70, so that the electrode material 30 passes through the gap having the distance C between the scraper 20 and the support 10. When the electrode material 30 passes through the gap having the distance C, the thickness and width of the electrode material 30 are restricted by the contact between the width-direction center portion and the width-direction end portions of the scraper 20, and the electrode material 30 is applied to the surface of the support 10, as shown in FIG. Figure 2 As shown, an electrode material film 34 based on an electrode material 30 is formed on a support 10 .
[0061] Furthermore, when the electrode material 30 passes through the gap having the distance C, the central portion in the width direction of the scraper 20 is vibrated by the vibrator 60, and the vibration is propagated to the electrode material 30, and a shear force is applied, thereby causing a decrease in viscosity and an increase in fluidity at least in the contact portion between the electrode material 30 and the central portion in the width direction of the scraper 20. As a result, it is presumed that, as described above, at least the surface of the electrode material film 34 formed by applying to the support 10 has a uniform surface shape, and an electrode material film 34 with less thickness deviation is formed.
[0062] like Figure 1 As shown, at least a portion of the electrode material 30 supplied to the support 10 and before the thickness and width of the electrode material 30 are restricted forms a reservoir 32 in the area clamped by the support 10 and the scraper 20. The electrode material is preferably supplied to the reservoir continuously or intermittently. From the viewpoint of obtaining an electrode material film with less thickness deviation, the ratio X:Y of the amount of electrode material supplied to the reservoir and the amount of electrode material film formed on the support is preferably 1:0.1 to 1:1 on a mass basis, more preferably 1:0.5 to 1:0.99, further preferably 1:0.80 to 1:0.99, and particularly preferably 1:0.90 to 1:0.99.
[0063] exist Figure 1and Figure 2 In FIG. 1 , the support body 10 is shown to be transported and moved along the arrow direction (ie, a certain direction) relative to the fixed scraper 20 , but the present invention is not limited to this method.
[0064] In the method for manufacturing an electrode molded body involved in the present invention, as long as the surface of the support body and the scraper move relative to each other, in addition to the above-mentioned method, it can also be a method in which the scraper is moved in one direction relative to the fixed support body, or it can be a method in which both the support body and the scraper are moved in one direction respectively.
[0065] However, in order to continuously form an electrode material film, it is preferable to use a long support and to use a method in which the long support is transported and moved relative to a fixed scraper.
[0066] Hereinafter, the support, the scraper, and the electrode material used in this step will be described.
[0067] [Support]
[0068] The support used in this process is not particularly limited as long as it is a support that can form an electrode material film on the surface. In particular, from the viewpoint of continuously forming an electrode material film, it is preferred to use a long-sized support. In the case of a long-sized support, its width can be determined according to the size of the electrode material film and the width (length) of the central portion of the scraper in the width direction.
[0069] As the support, specifically, a current collector is mentioned as a preferred support.
[0070] The current collector which is an example of the support is not particularly limited, and a known current collector (positive electrode current collector and negative electrode current collector) can be used.
[0071] Examples of the positive electrode current collector include aluminum, aluminum alloys, stainless steel, nickel, and titanium. The positive electrode current collector is preferably aluminum or an aluminum alloy. The positive electrode current collector may be aluminum having a coating layer containing one or more of carbon, nickel, titanium, silver, gold, platinum, and vanadium oxide on the surface.
[0072] Examples of the negative electrode current collector include aluminum, copper, copper alloys, stainless steel, nickel, and titanium. The negative electrode current collector is preferably aluminum, copper, copper alloys, or stainless steel, more preferably copper or a copper alloy. The negative electrode current collector may be copper or stainless steel having a coating layer containing one or more of carbon, nickel, titanium, silver, and lithium on the surface.
[0073] As the current collector, aluminum foil (including aluminum foil having the above-mentioned coating layer on the surface) and copper foil (including copper foil having the above-mentioned coating layer on the surface) are preferred. Usually, aluminum foil is used as the current collector in the positive electrode. Usually, copper foil is used as the current collector in the negative electrode.
[0074] In addition, the current collector used as a support may be a laminate of a metal layer and a resin film exemplified as the above-mentioned positive electrode current collector or negative electrode current collector. As the resin film used for the laminate, resin films such as polyethylene terephthalate (PET) film, polypropylene (PP) film, polyethylene (PE) film, cyclic olefin polymer (COP, COC) film, triacetyl cellulose (TAC) film, polyimide (PI) film, and polyamide (PA) film may be cited.
[0075] Furthermore, as an example of the support, a release material can be mentioned.
[0076] Examples of the release material as an example of the support include release paper (for example, release paper manufactured by LINTEC Corporation), a film having a release layer, and paper having a release layer. Among them, release paper is preferred.
[0077] Furthermore, when a release material is used as the support, the electrode material film formed on the release material can be transferred to the current collector by utilizing the releasability of the release material.
[0078] From the viewpoint of transportability and the like, the average thickness of the support (preferably a current collector) is preferably 3 μm or more, more preferably 5 μm or more, and particularly preferably 10 μm or more.
[0079] From the viewpoint of flexibility and lightness, the average thickness is preferably 100 μm or less, more preferably 70 μm or less, and particularly preferably 50 μm or less.
[0080] The average thickness of the support is the arithmetic average of thicknesses at three locations measured by cross-sectional observation. A known microscope (for example, a scanning electron microscope) can be used for cross-sectional observation.
[0081] The size of the support is not limited and may be determined according to the size of the electrode molded body to be produced, the sizes of various members used in the production process, and the like.
[0082] Furthermore, in this process, a conveying mechanism (e.g., equivalent to Figure 1 and Figure 2 The movable stage 70) is not limited and a known conveying mechanism can be used.
[0083] As a conveying mechanism for the support body, for example, a belt conveyor, a linear slide guide, a cross roller conveyor, etc. can be used.
[0084] [Scraper]
[0085] In this step, the scraper is placed at a constant distance from the surface of the support.
[0086] The setting position of the scraper can be set according to the gap between the surface of the support and the center of the width direction of the scraper, and the gap is set according to the film thickness of the electrode material film to be formed. In addition, "in a manner of maintaining a constant distance from the surface of the support", it is sufficient that the distance between the surface of the support and the front end of the center of the width direction of the scraper is substantially constant when the scraper moves relatively along the surface of the support. In "in a manner of maintaining a constant distance from the surface of the support", for example, the amplitude of the scraper caused by the vibration of the scraper is allowed. In addition, in "in a manner of maintaining a constant distance from the surface of the support", the position change of the surface of the support when the support is transported (the suspension of the support, the position change caused by the wrinkles generated on the support), the surface roughness on the surface of the support, etc. are also allowed. According to these contents, in the "manner of maintaining a constant distance from the surface of the support body", if the variation value of the distance between the surface of the support body and the center part of the width direction of the scraper when the scraper moves relative to the surface of the support body (i.e., the height of the gap) is within 3% or less than 20μm relative to the distance between the surface of the support body and the center part of the width direction of the scraper in a stopped state, then the variation is allowed.
[0087] Furthermore, the distance between the support surface and the width center of the blade (ie, the height of the gap) may vary slightly in the width direction, but such variation is permitted as long as it is within 3% or within 20 μm.
[0088] In addition, in the case of "maintaining a constant distance from the surface of the support body", as long as the distance between the surface of the support body and the front ends of the two end portions in the width direction of the scraper is kept substantially constant when the scraper moves relatively along the surface of the support body. In this way, the width of the electrode material can be effectively limited. Moreover, by maintaining the distance between the surface of the support body and the front ends of the two end portions in the width direction of the scraper substantially constant, the contact between the two end portions in the width direction of the scraper and the support body can be suppressed. In addition, in the distance between the surface of the support body and the front ends of the two end portions in the width direction of the scraper, the allowable value of "maintaining substantially constant" is the same as the allowable value of the variation value of the distance between the surface of the support body and the central portion in the width direction of the scraper.
[0089] The scraper is a component having a plate-like shape, but the shape, size, material, etc. of the contact portion that contacts the electrode material can be appropriately determined based on the type of electrode material (type of electrode active material, solid content concentration, composition of electrolyte (viscosity, surface tension), etc.), the size and thickness of the electrode material film formed, etc.
[0090] Furthermore, it is preferred that the portion of the scraper that contacts the electrode material does not easily adhere to the electrode material. For example, it is preferred that at least the surface of the scraper exhibits releasability.
[0091] For example, the scraper may be made of fluorine-based resin such as polytetrafluoroethylene (PTFE), resin such as polyetheretherketone (PEEK), metal such as stainless steel, aluminum, iron, superhard alloy, or ceramic.
[0092] Furthermore, in order to impart mold release properties to the surface, the blade may include a surface layer exhibiting mold release properties (for example, a surface layer containing a fluorine-based resin, a surface layer containing silicon-based particles and a resin).
[0093] Furthermore, from the viewpoint of improving the friction resistance, the blade may have a high hardness coating of titanium oxide, titanium nitride (TiN), tungsten carbide or the like on the metal or ceramic blade body.
[0094] In this step, from the viewpoint of obtaining an electrode material film with less variation in thickness, the friction coefficient μ1 between the contact portion of the scraper and the electrode material is preferably smaller than the friction coefficient μ2 between the electrode material and the support.
[0095] It is presumed that by satisfying the relationship of friction coefficient μ1<friction coefficient μ2, the electrode material is easily transferred to the support side and the electrode material is more easily applied to the support surface, resulting in an electrode material film with less thickness variation.
[0096] The friction coefficient μ1 and the friction coefficient μ2 are obtained by forming an electrode material layer from an electrode material and measuring the friction coefficient between the electrode material layer and a blade or a support.
[0097] Specifically, first, 5 to 20 g of the electrode material is filled into a battery (size: cylinder with a diameter of 20 to 30 mm and a height of 20 to 30 mm), and voids in the electrode material (ie, air) are removed to form an electrode material layer.
[0098] The obtained electrode material layer is placed on a scraper or a support, and a counterweight of 100 g to 1000 g is further placed on the electrode material layer. Then, the electrode material layer is slid laterally on the scraper or the support by a tensile tester (lateral sliding speed: 5 mm / sec). The friction coefficient is obtained by plotting the relationship between the load in the vertical direction based on the counterweight obtained by the lateral sliding and the resistance measured by the tensile tester.
[0099] In addition, when the scraper or support cannot be directly used for the above-mentioned measurement, only the surface of the scraper or support can be taken out, or a measurement sample having the same composition and surface properties as the surface of the scraper or support can be prepared and used for measurement.
[0100] The above measurement was performed in a dry room environment of 21° C. and 0% RH (dew point temperature −60° C.).
[0101] (Vibration of scraper)
[0102] In this process, the central portion of the scraper in the width direction is vibrated, but any vibration that can apply shearing based on the vibration to the electrode material in contact is sufficient. In addition, when the central portion of the scraper in the width direction is vibrated, the two ends of the scraper in the width direction may or may not vibrate. From the perspective of forming an electrode material film with a rectangular cross section, it is preferred that the two ends of the scraper in the width direction do not vibrate or vibrate less than the central portion of the scraper in the width direction.
[0103] In addition, the vibration direction when the blade is vibrated is not particularly limited.
[0104] The amplitude of the vibration of the scraper is, for example, preferably 1 μm to 60 μm, and more preferably 6 μm to 10 μm.
[0105] The vibration frequency of the scraper is preferably, for example, 100 Hz to 1000 Hz, and more preferably 200 Hz to 1000 Hz. In addition, the vibration frequency of the scraper may include a plurality of frequencies. For example, the vibration of the scraper may be a vibration in which a plurality of frequency peaks such as 150 Hz, 300 Hz, and 450 Hz are detected.
[0106] Here, the amplitude and frequency of the vibration can be measured by an acceleration sensor or a vibration measuring device. In addition, when measuring the vibration of the scraper, when multiple frequency peaks are detected, the frequency of the minimum value is set as the "frequency of the vibration of the scraper", and the amplitude at this frequency is set as the "amplitude of the vibration of the scraper". For example, with respect to the vibration of the scraper, when multiple frequency peaks such as 150 Hz, 300 Hz and 450 Hz are detected, 150 Hz is set as the "frequency of the vibration of the scraper", and the amplitude at the frequency of 150 Hz is set as the "amplitude of the vibration of the scraper".
[0107] Furthermore, from the viewpoint of obtaining an electrode material film with less thickness deviation, the ratio A:B of the amplitude A of the width center of the vibrating scraper to the thickness B of the electrode material film is preferably 1:10 to 1:200, more preferably 1:15 to 1:100, and further preferably 1:20 to 1:80.
[0108] It is speculated that by satisfying the above ratio A:B of 1:1 to 1:200, vibration-based shearing can be effectively applied to the contacting electrode material, and the viscosity of the electrode material can be easily reduced and the fluidity can be improved, thereby obtaining an electrode material film with less thickness deviation.
[0109] Here, the thickness B of the electrode material film is measured by the same method as the average thickness of the support.
[0110] In this step, the vibrator for vibrating the width center of the scraper is not particularly limited as long as it can vibrate the scraper, and examples thereof include pneumatic vibrators, motor vibrators, piezoelectric vibrators, ultrasonic vibrators, and the like.
[0111] (Pressure applied to electrode material)
[0112] In this process, the thickness and width of the electrode material supplied to the support are restricted by vibrating the widthwise center of the scraper while relatively moving along the support surface. At this time, pressure is applied to the electrode material in contact with the widthwise center of the scraper.
[0113] The pressure applied to the electrode material in contact with the scraper is not particularly limited as long as it can form an electrode material film with the target shape, density, surface properties, etc., including thickness, and can be appropriately determined based on the physical properties of the electrode material (fluidity such as yield value, viscosity, surface tension, etc., adhesion to the support body, etc.).
[0114] For example, when the electrode material has a yield value, it is preferred to apply pressure to the electrode material in contact with the scraper so that the yield value of the electrode material is exceeded and the electrode material begins to flow. It is speculated that by setting it in this way, the fluidity of the electrode material is improved throughout the thickness direction of the electrode material, so it is easy to obtain an electrode material film with less thickness deviation.
[0115] Examples of methods for changing the pressure applied to the electrode material in contact with the scraper include adjusting the distance between the support surface and the scraper tip, the pressure of pressing the scraper toward the support surface, and the scraper's own weight.
[0116] The method of arranging the scraper in a manner of maintaining a constant distance from the support surface is not limited to the following. Figure 1 and Figure 2 The method of using the pressurizing shaft and the air cylinder described in the specification can be applied to a known method.
[0117] In addition, it is preferable to adopt a method that can adjust the pressure with which the scraper is pressed toward the support surface, such as a method using a pressurizing shaft and an air cylinder.
[0118] [Electrode materials]
[0119] The electrode material used in this step contains an electrode active material and has a solid content concentration of 30 volume % or more. Here, "solid content concentration of 30 volume % or more" means that the content of the solid content relative to the total volume of the electrode material is 30 volume % or more.
[0120] The solid content concentration in the electrode material is preferably 40% by volume or more, and more preferably 45% by volume or more. In addition, the upper limit of the solid content concentration in the electrode material may be 100% by volume or less, or may be less than 100% by volume.
[0121] Here, the solid content concentration of the electrode material is calculated based on the composition ratio of each component included in the electrode material and the specific gravity of these components.
[0122] The electrode material includes an electrode active material, but may include components other than the electrode active material as required. In addition, the electrode active material constitutes at least a part of the solid content.
[0123] Hereinafter, components contained in the electrode material will be described.
[0124] (Electrode Active Material)
[0125] The electrode active material is a substance that can absorb and release ions of a metal element belonging to Group 1 or Group 2 of the periodic table.
[0126] Examples of the electrode active material include a positive electrode active material and a negative electrode active material.
[0127] - Positive electrode active material -
[0128] The positive electrode active material is not limited, and known active materials used in positive electrodes can be used. The positive electrode active material is preferably a positive electrode active material that can reversibly absorb and release lithium ions.
[0129] Specific examples of the positive electrode active material include transition metal oxides and elements that can form a complex with lithium (for example, sulfur). Among the above, the positive electrode active material is preferably a transition metal oxide.
[0130] The transition metal oxide is preferably a transition metal oxide containing at least one transition metal element (hereinafter referred to as “element Ma”) selected from the group consisting of Co (cobalt), Ni (nickel), Fe (iron), Mn (manganese), Cu (copper) and V (vanadium).
[0131] When the transition metal oxide contains Li and the element Ma, the molar ratio of Li to Ma (Li / Ma) is preferably 0.3 to 2.2.
[0132] Furthermore, the transition metal oxide may contain at least one transition metal element (hereinafter referred to as "element Mb") selected from the group consisting of Group 1 elements other than lithium, Group 2 elements, Al (aluminum), Ga (gallium), In (indium), Ge (germanium), Sn (tin), Pb (lead), Sb (antimony), Bi (bismuth), Si (silicon), P (phosphorus) and B (boron). The content of element Mb is preferably 0 mol% to 30 mol% relative to the amount of element Ma.
[0133] Examples of the transition metal oxide include transition metal oxides having a layered rock salt structure, transition metal oxides having a spinel structure, lithium-containing transition metal phosphate compounds, lithium-containing transition metal halophosphate compounds, and lithium-containing transition metal silicate compounds.
[0134] Examples of transition metal oxides having a layered rock salt structure include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).
[0135] Examples of transition metal oxides having a spinel structure include LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8, and Li2NiMn3O8.
[0136] As lithium-containing transition metal phosphate compounds, for example, there can be mentioned olivine-type iron phosphates (for example, LiFePO4 and Li3Fe2(PO4)3), pyrophosphate iron salts (for example, LiFeP2O7), cobalt phosphates (for example, LiCoPO4) and monoclinic NASICON-type vanadium phosphates (for example, Li3V2(PO4)3 (lithium vanadium phosphate)).
[0137] Examples of lithium-containing transition metal halophosphate compounds include iron fluorophosphates (eg, Li2FePO4F), manganese fluorophosphates (eg, Li2MnPO4F), and cobalt fluorophosphates (eg, Li2CoPO4F).
[0138] Examples of lithium-containing transition metal silicate compounds include Li 2 FeSiO 4 , Li 2 MnSiO 4 , and Li 2 CoSiO 4 .
[0139] The transition metal oxide is preferably a transition metal oxide having a layered rock salt structure, and more preferably selected from LiCoO2 (lithium cobalt oxide [LCO]), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]) and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 At least one compound selected from the group consisting of O2 (lithium nickel manganese cobalt oxide [NMC]).
[0140] The positive electrode active material may be a commercially available product or a synthetic product produced by a known method (eg, calcination method). For example, the positive electrode active material obtained by calcination method may be washed with water, an acidic aqueous solution, an alkaline aqueous solution or an organic solvent.
[0141] Furthermore, the positive electrode active material may have a carbon coating on its surface.
[0142] The shape of the positive electrode active material is not limited, but is preferably in the form of particles from the viewpoint of handleability.
[0143] The volume average particle size of the positive electrode active material is not limited, and can be, for example, 0.1 μm to 50 μm. The volume average particle size of the positive electrode active material is preferably 0.3 μm to 40 μm, and more preferably 0.5 μm to 30 μm.
[0144] The volume average particle size of the positive electrode active material is 0.3 μm or more, so that the aggregate of the electrode material can be easily formed and the splashing of the electrode material can be suppressed during operation. The volume average particle size of the positive electrode active material is 40 μm or less, so that the thickness of the electrode molded body can be easily adjusted and the generation of voids during the molding process can be suppressed.
[0145] The volume average particle size of the positive electrode active material is measured by the following method.
[0146] A dispersion containing 0.1% by mass of the positive electrode active material is prepared by mixing the positive electrode active material with a solvent (e.g., heptane, octane, toluene or xylene). The dispersion irradiated with 1 kHz ultrasonic waves for 10 minutes is set as a measurement sample. Using a laser diffraction / scattering particle size distribution measuring device (e.g., LA-920 manufactured by HORIBA, Ltd.) and at a temperature of 25°C, 50 data readings are performed to determine the volume average particle size. A quartz colorimetric cell is used in the measuring cell. The above measurement is performed using 5 samples, and the average of the measured values is set as the volume average particle size of the positive electrode active material. For other detailed conditions, refer to "JIS Z 8828:2013" as needed.
[0147] As a method for adjusting the particle size of the positive electrode active material, for example, there can be mentioned a method using a pulverizer, a disintegrator, or a classifier. Also, as a method for adjusting the particle size of the positive electrode active material, a known grinding method can be applied.
[0148] The electrode material may contain a single positive electrode active material, or may contain two or more positive electrode active materials.
[0149] Furthermore, even when the electrode material includes one type of positive electrode active material, positive electrode active materials having different particle sizes may be used in combination.
[0150] The content of the positive electrode active material relative to the total volume of the electrode material is preferably 30% by volume to 60% by volume, more preferably 35% by volume to 55% by volume, and even more preferably 40% by volume to 50% by volume.
[0151] - Negative electrode active material -
[0152] The negative electrode active material is not limited, and known active materials used in negative electrodes can be used. The negative electrode active material is preferably a negative electrode active material that can reversibly absorb and release lithium ions.
[0153] As the negative electrode active material, for example, carbonaceous materials, metal oxides (for example, tin oxide), silicon oxide, metal composite oxides, lithium monomers, lithium alloys (for example, lithium aluminum alloys) and metals that can form alloys with lithium (for example, Sn, Si and In) can be cited. Among the above, from the viewpoint of reliability, the negative electrode active material is preferably a carbonaceous material or a lithium composite oxide.
[0154] Carbonaceous materials are materials consisting substantially of carbon.
[0155] Examples of carbonaceous materials include petroleum pitch, carbon black (e.g., acetylene black), graphite (e.g., natural graphite and artificial graphite (e.g., vapor-grown graphite)), hard carbon, and carbonaceous materials obtained by calcining synthetic resins (e.g., polyacrylonitrile (PAN) and furfuryl alcohol resin). Examples of carbonaceous materials include carbon fibers (e.g., polyacrylonitrile carbon fibers, cellulose carbon fibers, pitch carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol) carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers). Examples of graphite include mesophase microspheres, graphite whiskers, and flat graphite.
[0156] In the present invention, "flat plate shape" means a shape having two main planes facing in opposite directions.
[0157] As the metal composite oxide, a metal composite oxide capable of occluding and releasing lithium is preferred.
[0158] From the viewpoint of high current density charge and discharge characteristics, the metal composite oxide capable of occluding and releasing lithium preferably contains at least one element selected from the group consisting of titanium and lithium.
[0159] The metal oxide and the metal composite oxide are particularly preferably amorphous oxides.
[0160] The metal oxide and the metal composite oxide are also preferably chalcogenides. Chalcogenides are reaction products between metal elements and elements of Group 16 in the periodic table.
[0161] Among the compound group consisting of amorphous oxides and chalcogenides, amorphous oxides and chalcogenides of semimetallic elements are also preferred, and oxides and chalcogenides of at least one element selected from the group consisting of elements of Groups 13 to 15 in the periodic table, Al, Ga, Si, Sn, Ge, Pb, Sb and Bi are more preferred.
[0162] The negative electrode active material preferably further contains titanium. The volume change during the storage and release of lithium ions is small, so the rapid charge and discharge characteristics are excellent, and from the perspective of suppressing electrode degradation and increasing the life of the lithium ion secondary battery, the negative electrode active material containing titanium is preferably Li4Ti5O 12 (lithium titanate [LTO]).
[0163] The negative electrode active material may be a commercially available product or a synthetic product produced by a known method (eg, calcination method). For example, the negative electrode active material obtained by calcination method may be washed with water, an acidic aqueous solution, an alkaline aqueous solution or an organic solvent.
[0164] The negative electrode active material is available as, for example, CGB20 (Nippon Graphite Industry Co., Ltd.).
[0165] The composition of the negative electrode active material was measured using inductively coupled plasma (ICP) emission spectrometry.
[0166] The shape of the negative electrode active material is not limited, but is preferably in the form of particles from the viewpoint of easy handling and easy control of uniformity during mass production.
[0167] The volume average particle size of the negative electrode active material is preferably 0.1 μm to 60 μm, more preferably 0.3 μm to 50 μm, and particularly preferably 0.5 μm to 40 μm.
[0168] The volume average particle size of the negative electrode active material is measured by a method based on the method for measuring the volume average particle size of the positive electrode active material described above.
[0169] As a method of adjusting the particle size of the negative electrode active material, there is mentioned, for example, a method of using a pulverizer or a classifier.
[0170] The electrode material may contain a single negative electrode active material or may contain two or more negative electrode active materials.
[0171] The content of the negative electrode active material relative to the total volume of the electrode material is preferably 30% by volume to 60% by volume, more preferably 35% by volume to 57% by volume, and even more preferably 45% by volume to 55% by volume.
[0172] The surfaces of the positive electrode active material and the negative electrode active material may be coated with a surface coating agent, respectively. As the surface coating agent, for example, a metal oxide containing Ti, Nb, Ta, W, Zr, Si or Li may be cited. As the above-mentioned metal oxide, for example, titanate spinel, tantalum oxide, niobium oxide and lithium niobate compound may be cited.
[0173] (Inorganic solid electrolyte)
[0174] From the viewpoint of improving battery performance (for example, discharge capacity and output characteristics), the electrode material preferably contains an inorganic solid electrolyte.
[0175] Here, the “solid electrolyte” refers to a solid electrolyte that can move ions inside.
[0176] The inorganic solid electrolyte is contained in the solid component.
[0177] Inorganic solid electrolytes are not electrolytes that contain organic matter as the main ion conductivity material, and therefore are clearly distinguished from organic solid electrolytes (for example, polymer electrolytes represented by polyethylene oxide (PEO) and organic electrolyte salts represented by lithium bis(trifluoromethanesulfonyl)imide (LiTFSI)). In addition, inorganic solid electrolytes are solid in a stable state, so they are not dissociated or freed into cations or anions. Therefore, they are also clearly distinguished from inorganic electrolyte salts that dissociate or free into cations or anions in electrolytes and polymers (for example, LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI) and LiCl).
[0178] The inorganic solid electrolyte is not limited as long as it has ion conductivity of a metal element belonging to Group 1 or Group 2 of the periodic table, but generally does not have electron conductivity.
[0179] When the molded article for an electrode obtained by the method for producing a molded article for an electrode according to the present invention is used in a lithium ion battery, the inorganic solid electrolyte preferably has ion conductivity of lithium ions.
[0180] Examples of the inorganic solid electrolyte include sulfide-based inorganic solid electrolytes and oxide-based inorganic solid electrolytes.
[0181] Among the above, the inorganic solid electrolyte is preferably a sulfide-based inorganic solid electrolyte from the viewpoint of being able to form a good interface between the active material and the inorganic solid electrolyte.
[0182] -Sulfide-based inorganic solid electrolyte-
[0183] The sulfide-based inorganic solid electrolyte preferably contains sulfur atoms (S), has ion conductivity of a metal element belonging to Group 1 or Group 2 of the periodic table, and has electron insulating properties.
[0184] The sulfide-based inorganic solid electrolyte more preferably contains at least Li, S, and P and has lithium ion conductivity. The sulfide-based inorganic solid electrolyte may further contain elements other than Li, S, and P as necessary.
[0185] Examples of the sulfide-based inorganic solid electrolyte include an inorganic solid electrolyte having a composition represented by the following formula (A).
[0186] L a1 M b1 P c1 S d1 A e1 :Formula (A)
[0187] In formula (A), L represents at least one element selected from the group consisting of Li, Na and K, and is preferably Li.
[0188] In formula (A), M represents at least one element selected from the group consisting of B, Zn, Sn, Si, Cu, Ga, Sb, Al and Ge, preferably B, Sn, Si, Al or Ge, more preferably Sn, Al or Ge.
[0189] In formula (A), A represents at least one element selected from the group consisting of I, Br, Cl and F, preferably I or Br, and more preferably I.
[0190] In formula (A), a1 represents 1 to 12, preferably 1 to 9, and more preferably 1.5 to 4.
[0191] In formula (A), b1 represents 0 to 1, and more preferably 0 to 0.5.
[0192] In formula (A), c1 represents 1.
[0193] In formula (A), d1 represents 2 to 12, preferably 3 to 7, and more preferably 3.25 to 4.5.
[0194] In formula (A), e1 represents 0-5, preferably 0-3, and more preferably 0-1.
[0195] In formula (A), b1 and e1 are preferably 0, b1 and e1 are 0, and the ratio of a1, c1 and d1 (i.e., a1:c1:d1) is more preferably 1-9:1:3-7, b1 and e1 are 0, and the ratio of a1, c1 and d1 (i.e., a1:c1:d1) is particularly preferably 1.5-4:1:3.25-4.5.
[0196] The composition ratio of each element can be controlled by adjusting the blending amount of the raw material compound when producing the sulfide-based inorganic solid electrolyte, for example.
[0197] The sulfide-based inorganic solid electrolyte may be amorphous (glass), or may be crystallized (glass ceramic), or may be only partially crystallized. As the above-mentioned sulfide-based inorganic solid electrolyte, for example, Li-PS-based glass containing Li, P and S and Li-PS-based glass ceramics containing Li, P and S can be cited. Among the above, the sulfide-based inorganic solid electrolyte is preferably Li-PS-based glass.
[0198] The lithium ion conductivity of the sulfide inorganic solid electrolyte is preferably 1×10 -4 S / cm or more, more preferably 1×10 -3 S / cm or more. The upper limit of the lithium ion conductivity of sulfide-based inorganic solid electrolytes is not limited, for example, it is actually 1×10 -1 S / cm or less.
[0199] Sulfide-based inorganic solid electrolytes can be produced, for example, by (1) a reaction between lithium sulfide (Li2S) and phosphorus sulfide (e.g., phosphorus pentasulfide (P2S5)), (2) a reaction between lithium sulfide and at least one of monomeric phosphorus and monomeric sulfur, or (3) a reaction between lithium sulfide, phosphorus sulfide (e.g., phosphorus pentasulfide (P2S5)) and at least one of monomeric phosphorus and monomeric sulfur.
[0200] The molar ratio of Li2S to P2S5 (Li2S:P2S5) in the production of Li-PS glass and Li-PS glass ceramics is preferably 65:35 to 85:15, and more preferably 68:32 to 77:23. By setting the molar ratio of Li2S to P2S5 within the above range, the lithium ion conductivity can be further improved.
[0201] Examples of the sulfide-based inorganic solid electrolyte include compounds obtained using a raw material composition containing Li 2 S and a sulfide of an element of Group 13 to Group 15.
[0202] Examples of the raw material composition include Li2S-P2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2, Li2S-GeS2-ZnS, Li2S -Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, Li2S-Al2S3, Li2S- SiS2-Al2S3, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4 and Li 10 GeP2S 12 Among the above, from the viewpoint of high lithium ion conductivity, the raw material composition is preferably Li2S-P2S5, Li2S-GeS2-Ga2S3, Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li2S-LiI-Li2O-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-GeS2-P2S5 or Li 10 GeP2S 12 , more preferably Li2S-P2S5, Li 10 GeP2S 12 or Li2S-P2S5-SiS2.
[0203] As a method for producing a sulfide-based inorganic solid electrolyte using the above-mentioned raw material composition, an amorphization method is mentioned, for example.
[0204] Examples of the amorphization method include a mechanical milling method and a melt quenching method. Among the above, the mechanical milling method is preferred from the viewpoint of being able to perform treatment at room temperature and simplifying the production process.
[0205] -Oxide-based inorganic solid electrolytes-
[0206] The oxide-based inorganic solid electrolyte preferably contains oxygen atoms (O), has ion conductivity of a metal element belonging to Group 1 or Group 2 of the periodic table, and has electron insulating properties.
[0207] The ionic conductivity of the oxide-based inorganic solid electrolyte is preferably 1×10 -6 S / cm or more, more preferably 5×10 -6 S / cm or more, particularly preferably 1×10 -5 S / cm or more. The upper limit of the ion conductivity of oxide-based inorganic solid electrolytes is not limited, for example, it is actually 1×10 -1 S / cm or less.
[0208] Examples of the oxide-based inorganic solid electrolyte include the following compounds. However, the oxide-based inorganic solid electrolyte is not limited to the following compounds.
[0209] (1)Li xa La ya TiO3 (hereinafter referred to as "LLT". xa satisfies 0.3≤xa≤0.7, and ya satisfies 0.3≤ya≤0.7.)
[0210] (2)Li xb La yb Zr zb M bb mb O nb (M bb is at least one element selected from the group consisting of Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In and Sn. xb satisfies 5≤xb≤10, yb satisfies 1≤yb≤4, zb satisfies 1≤zb≤4, mb satisfies 0≤mb≤2, and nb satisfies 5≤nb≤20. )
[0211] (3)Li xc B yc M cc zc O nc (M cc is at least one element selected from the group consisting of C, S, Al, Si, Ga, Ge, In and Sn. xc satisfies 0≤xc≤5, yc satisfies 0≤yc≤1, zc satisfies 0≤zc≤1, and nc satisfies 0≤nc≤6. )
[0212] (4)Li xd (Al, Ga) yd (Ti, Ge) zd Si ad P md O nd (xd satisfies 1≤xd≤3, yd satisfies 0≤yd≤1, zd satisfies 0≤zd≤2, ad satisfies 0≤ad≤1, md satisfies 1≤md≤7, and nd satisfies 3≤nd≤13.)
[0213] (5)Li(3-2xe) M ee xe D ee O(xe satisfies 0≤xe≤0.1, M ee represents a divalent metal atom, D ee represents a halogen atom or a combination of two or more halogen atoms. )
[0214] (6)Li xf Si yf O zf (xf satisfies 1≤xf≤5, yf satisfies 0<yf≤3, and zf satisfies 1≤zf≤10.)
[0215] (7)Li xg S yg O zg (xg satisfies 1≤xg≤3, yg satisfies 0<yg≤2, and zg satisfies 1≤zg≤10.)
[0216] (8)Li3BO3
[0217] (9)Li3BO3-Li2SO4
[0218] (10)Li2O-B2O3-P2O5
[0219] (11)Li2O-SiO2
[0220] (12)Li6BaLa2Ta2O 12
[0221] (13)Li3PO (4-3 / 2w) N w (w satisfies w<1.)
[0222] (14) Li with LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zn 0.25 GeO4
[0223] (15) La with a perovskite crystal structure 0.55 Li 0.35 TiO3
[0224] (16) LiTi2P3O with NASICON (Natrium super ionic conductor) crystal structure 12
[0225] (17)Li 1+xh+yh (Al, Ga) xh (Ti, Ge)2-xh Si yh P 3-yh O 12 (xh satisfies 0≤xh≤1, yh satisfies 0≤yh≤1.)
[0226] (18) Li7La3Zr2O with garnet crystal structure 12 (Hereinafter, referred to as "LLZ".)
[0227] As an oxide-based inorganic solid electrolyte, a phosphorus compound containing Li, P and O is also preferred. As a phosphorus compound containing Li, P and O, for example, lithium phosphate (Li3PO4), LiPON in which a part of the oxygen of lithium phosphate is replaced by nitrogen, and LiPOD1 (D1 is at least one element selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt and Au.).
[0228] As the oxide-based inorganic solid electrolyte, LiAlON (Al is at least one element selected from the group consisting of Si, B, Ge, Al, C, and Ga) is also preferred.
[0229] Among the above, the oxide-based inorganic solid electrolyte is preferably LLT, Li xb La yb Zr zb M bb mb O nb (M bb , xb, yb, zb, mb and nb are as described above. ), LLZ, Li3BO3, Li3BO3-Li2SO4 or Li xd (Al, Ga) yd (Ti, Ge) zd Si ad P md O nd (xd, yd, zd, ad, md and nd are as described above.), more preferably LLT, LLZ, LAGP (Li 1.5 Al 0.5 Ge 1.5 (PO4)3) or LATP([Li 1.4 Ti2Si 0.4 P 2.6 O 12 ]-AlPO4), particularly preferably LLZ.
[0230] The inorganic solid electrolyte is preferably in a particle form.
[0231] The volume average particle size of the inorganic solid electrolyte is preferably 0.01 μm or more, and more preferably 0.1 μm or more. The upper limit of the volume average particle size of the inorganic solid electrolyte is preferably 100 μm or less, and more preferably 50 μm or less.
[0232] The volume average particle size of the inorganic solid electrolyte is measured by a method based on the method for measuring the volume average particle size of the positive electrode active material described above.
[0233] The electrode material may contain a single inorganic solid electrolyte or may contain two or more inorganic solid electrolytes.
[0234] When the electrode material contains an inorganic solid electrolyte, the content of the inorganic solid electrolyte relative to the total volume of the electrode material is more preferably 25% to 35% by volume from the viewpoint of reducing interface resistance and maintaining battery characteristics (for example, improving cycle characteristics).
[0235] (Conductive additive)
[0236] From the viewpoint of improving the electron conductivity of the active material, the electrode material preferably contains a conductive auxiliary agent. The conductive auxiliary agent is not limited, and a known conductive auxiliary agent can be used.
[0237] The conductive auxiliary agent is contained in the solid component.
[0238] As conductive aids, for example, graphite (for example, natural graphite and artificial graphite), carbon black (for example, acetylene black, Ketjen black and furnace black), amorphous carbon (for example, needle coke), carbon fiber (for example, vapor-grown carbon fiber and carbon nanotube), other carbonaceous materials (for example, graphene and fullerene), metal powder (for example, copper powder and nickel powder), metal fiber (for example, copper fiber and nickel fiber) and conductive polymers (for example, polyaniline, polypyrrole, polythiophene, polyacetylene and polyphenylene derivatives) can be cited.
[0239] The electrode material may contain a single conductive aid or two or more conductive aids.
[0240] When the electrode material contains a conductive aid, from the viewpoint of improving the electronic conductivity of the active material, the content of the conductive aid is preferably 0.05 volume % to 5 volume %, more preferably 0.1 volume % to 4 volume %, and even more preferably 0.5 volume % to 3 volume % relative to the total volume of the electrode material.
[0241] (Electrolyte)
[0242] The electrode material may contain an electrolyte.
[0243] The electrolyte is contained in the liquid component.
[0244] The electrolyte is not limited, and a known electrolyte can be used. For example, an electrolyte containing an electrolyte and a solvent can be cited. As a specific electrolyte, for example, an electrolyte containing a lithium salt compound as an electrolyte and a carbonate compound as a solvent can be cited.
[0245] As the lithium salt compound, for example, lithium hexafluorophosphate can be mentioned. The electrolyte solution may contain a single lithium salt compound, or may contain two or more lithium salt compounds.
[0246] As carbonate compounds, for example, chain carbonate compounds such as ethyl methyl carbonate (also referred to as EMC), dimethyl carbonate (also referred to as DMC), diethyl carbonate (DEC) and cyclic carbonate compounds such as ethylene carbonate (also referred to as EC) and propylene carbonate (also referred to as PC) can be cited. The electrolyte can include a single carbonate compound, can include two or more carbonate compounds, and can also use more than one chain carbonate compound and more than one cyclic carbonate compound simultaneously.
[0247] Examples of the electrolyte contained in the electrolytic solution include the materials described in the above section "inorganic solid electrolyte".
[0248] As a component of the electrolytic solution, for example, an ionic liquid can be used. The ionic liquid can be used as an electrolyte or as a solvent.
[0249] The content of the electrolyte relative to the total volume of the electrode material is preferably 70% by volume or less, preferably 60% by volume or less, and more preferably 55% by volume or less. The content of the electrolyte in the electrode material is 70% by volume or less, thereby being able to suppress the electrolyte from seeping out when the electrode material is formed.
[0250] The lower limit of the content of the electrolyte solution in the electrode material is not limited, and may be 0 volume % or more, or may exceed 0 volume %.
[0251] The electrode material may contain, as a liquid component, a solvent other than the solvent contained as a component of the electrolytic solution (hereinafter, also simply referred to as a “solvent”).
[0252] Examples of the solvent include alcohol compound solvents, ether compound solvents, amide compound solvents, amino compound solvents, ketone compound solvents, aromatic compound solvents, aliphatic compound solvents, and nitrile compound solvents.
[0253] The boiling point of the solvent is preferably 50° C. or higher, more preferably 70° C. or higher, at normal pressure (ie, 1 atmosphere). The upper limit of the boiling point of the solvent is preferably 250° C. or lower, more preferably 220° C. or lower, at normal pressure (ie, 1 atmosphere).
[0254] The electrode material may contain a single solvent or two or more solvents.
[0255] The content of the liquid component (ie, the electrolyte solution and the solvent) relative to the total volume of the electrode material is preferably 70% by volume or less, preferably 60% by volume or less, and more preferably 55% by volume or less.
[0256] The content of the liquid component in the electrode material is 70 volume % or less, thereby being able to suppress the liquid component from seeping out when the electrode material is molded.
[0257] Furthermore, when the liquid component contains a solvent, degradation of battery performance can be suppressed.
[0258] The lower limit of the content of the liquid component in the electrode material is not limited, and may be 0 volume % or more, or may exceed 0 volume %.
[0259] In addition, the liquid component in the electrode material, that is, the component in the electrode material that is liquid at 25° C. is preferably liquid even at -10° C., and preferably liquid even at -20° C. That is, the component in the electrode material that is liquid at 25° C. is preferably a component that does not solidify at -10° C., and preferably a component that does not solidify at -20° C.
[0260] (Other ingredients)
[0261] The electrode material may contain a binder, a dispersant, other additives, etc. in addition to the above components.
[0262] Examples of the binder include fluorine-containing resins, hydrocarbon thermoplastic resins, acrylic resins, and urethane resins.
[0263] Furthermore, the dispersant may be any known dispersant as long as it can disperse the dispersion object.
[0264] Furthermore, as other additives, known additives added to electrode materials can be used.
[0265] (Method for preparing electrode material)
[0266] The electrode material can be prepared, for example, by mixing the electrode active material with the above-mentioned components other than the electrode active material, as necessary.
[0267] Examples of the mixing method include methods using a ball mill, a bead mill, a planetary mixer, a blade mixer, a roll mill, a kneader, or a disk mill.
[0268] (Supply of electrode materials)
[0269] The electrode material is supplied onto the support, but the supply method is not particularly limited. The supply of the electrode material onto the support may be performed intermittently or continuously.
[0270] The supply amount of the electrode material may be determined according to the size of the electrode material film to be formed.
[0271] 〔Other processes〕
[0272] The method for producing the electrode molded body according to the present invention may include other steps.
[0273] Examples of other steps include a step of pressing the electrode material film and a step of transferring the electrode material film formed on the release paper to the current collector when the support is release paper.
[0274] (Step of Pressurizing Electrode Material Film)
[0275] The method for producing a molded body for an electrode according to the present invention may include a step of pressurizing the electrode material film obtained in the above step.
[0276] Since the method for producing an electrode molded body according to the present invention includes a pressurizing step, the density of the electrode material can be increased and the density and thickness can be made uniform within a plane.
[0277] Examples of the pressurizing mechanism used in this step include a pressurizing roller pair and a punch.
[0278] When the electrode material is pressurized, the pressure is preferably 0.01 MPa to 100 MPa, more preferably 0.1 MPa to 50 MPa, and particularly preferably 0.2 MPa to 10 MPa.
[0279] In this step, multiple pressurizing mechanisms (eg, a pair of pressurizing rollers) may be used to pressurize the electrode material film in stages. By using multiple pressurizing mechanisms to pressurize the electrode material film in stages, the density and thickness of the electrode material can be made more uniform.
[0280] For example, by using a plurality of pressurizing roller pairs adjusted so that the gap between the rollers is gradually narrowed, the electrode material film can be pressurized in a step-by-step manner.
[0281] In this step, it is preferred that the pressurizing mechanism and the electrode material film (specifically, the support on which the electrode material film is formed) are relatively moved.
[0282] In the present invention, "moving the pressurizing mechanism and the electrode material film relative to each other" includes moving the pressurizing mechanism in one direction relative to the electrode material film, moving the electrode material film in one direction relative to the pressurizing mechanism, and moving the pressurizing mechanism and the electrode material film in one direction respectively, but preferably moving the electrode material film in one direction relative to the pressurizing mechanism.
[0283] The mechanism for moving the electrode material film (specifically, the support body on which the electrode material film is formed) is not limited, and a known conveying mechanism can be used, for example, a belt conveyor, a linear slide guide, and a cross roller conveyor.
[0284] In this step, from the viewpoint of improving moldability, the electrode material film heated at, for example, 30° C. to 100° C. may be pressed.
[0285] <<Molded article for sheet electrode>>
[0286] The sheet-like electrode molded body obtained by the method for producing a sheet-like electrode molded body according to the present invention has excellent in-plane uniformity of thickness and can therefore be used as various electrodes.
[0287] The sheet-shaped electrode molded body is preferably a molded body for an electrode of an all-solid-state secondary battery.
[0288] From the viewpoint of improving battery performance (for example, discharge capacity and output characteristics), the average thickness of the sheet-like electrode molded body is preferably 0.01 mm to 2 mm, more preferably 0.05 mm to 1.5 mm, and particularly preferably 0.1 mm to 1 mm.
[0289] The average thickness of the electrode molded body is measured by the same method as the average thickness of the support.
[0290] Example
[0291] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited thereto.
[0292] [Preparation of positive electrode material (P1)]
[0293] (1) After 13.4 g of LiPF6 (electrolyte) was mixed with a mixed solution of 45 g of ethylene carbonate (EC), 10 g of propylene carbonate (PC) and 45 g of diethyl carbonate (DEC), 2.3 g of vinylene carbonate (VC) was further mixed. 64 g of the obtained 115.7 g mixed solution was taken out and used as electrolyte X1.
[0294] (2) Using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION), 2 g of a conductive aid (Ketjen black: "Carbon ECP600JD" manufactured by Lion Specialty Chemicals Co., Ltd.) and 174 g of a positive electrode active material (iron phosphate: "LFP NCO M121" manufactured by Aleees) were stirred at 1500 rpm (revolutions per minute, the same below) for 30 seconds to prepare a kneaded product Y1 (176 g).
[0295] (3) Electrolyte X1 (64 g) was added to kneaded product Y1 (176 g), and the mixture was stirred at 1500 rpm for 120 seconds using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION) to obtain a positive electrode material (P1).
[0296] The obtained positive electrode material (P1) was a Bingham fluid having a yield value of 45 kPa, and the volume ratio of the solid component to the liquid component was 48:52.
[0297] [Preparation of negative electrode material (P2)]
[0298] (1) An electrolyte solution X1 (64 g) which was the same as the electrolyte solution used in the positive electrode material (P1) was prepared.
[0299] (2) A conductive aid (carbon black: "C-NERGY SUPER C45" manufactured by Imerys Graphite & Carbon) and a negative electrode active material ("MESOPHASE GRAPHITE POWDER A (MGP-A)" manufactured by China Steel Chemical Corporation) were weighed in a total amount of 159 g in a mass ratio of 2.7:63.4, and the two were stirred at 900 rpm for 18 seconds using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION) to prepare a kneaded product Z1.
[0300] (3) Electrolyte X1 (64 g) was added to kneaded product Z1 (159 g), and the mixture was stirred at 900 rpm for 30 seconds using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION) to obtain a negative electrode material (P2).
[0301] The obtained negative electrode material (P2) was a Bingham fluid having a yield value of 20 kPa, and the volume ratio of the solid component to the liquid component was 52:48.
[0302] [Preparation of positive electrode material (P3)]
[0303] (1) After 13.4 g of LiPF6 (electrolyte) was mixed with a mixed solution of 45 g of ethylene carbonate (EC), 10 g of propylene carbonate (PC) and 45 g of diethyl carbonate (DEC), 2.3 g of vinylene carbonate (VC) was further mixed. 62 g of the obtained 115.7 g of the mixed solution was taken out and used as electrolyte X2.
[0304] (2) Using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION), 4 g of a conductive additive (Ketjen black: “Carbon ECP600JD” manufactured by Lion Specialty Chemicals Co., Ltd.) and 174 g of a positive electrode active material (iron phosphate: “LFP NCO M121” manufactured by Alees) were stirred at 1500 rpm for 30 seconds to prepare a kneaded product Y2 (178 g).
[0305] (3) Electrolyte X2 (62 g) was added to kneaded product Y2 (178 g), and the mixture was stirred at 1500 rpm for 120 seconds using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION) to obtain a positive electrode material (P3).
[0306] The obtained positive electrode material (P3) was a Bingham fluid having a yield value of 60 kPa, and the volume ratio of the solid component to the liquid component was 47:53.
[0307] [Preparation of negative electrode material (P4)]
[0308] (1) An electrolyte solution X2 (62 g) which was the same as the electrolyte solution used for the positive electrode material (P3) was prepared.
[0309] (2) A conductive aid (carbon black: "C-NERGY SUPER C45" manufactured by Imerys Graphite & Carbon) and a negative electrode active material ("MESOPHASE GRAPHITE POWDER A (MGP-A)" manufactured by China Steel Chemical Corporation) were weighed in a total amount of 159 g in a mass ratio of 3.1:63, and the two were stirred at 900 rpm for 18 seconds using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION) to prepare a kneaded product Z2.
[0310] (3) Electrolyte X2 (62 g) was added to kneaded product Z2 (159 g), and the mixture was stirred at 900 rpm for 30 seconds using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION) to obtain a negative electrode material (P4).
[0311] The obtained negative electrode material (P4) was a Bingham fluid having a yield value of 30 kPa, and the volume ratio of the solid component to the liquid component was 53:47.
[0312] [Preparation of Supports (S1) to (S4)]
[0313] Support (S1): positive electrode current collector (aluminum foil, average thickness 20 μm, Ra 0.5 μm, EAA-218D, carbon-coated product manufactured by Korea JCC Co., Ltd.)
[0314] Support (S2): positive electrode current collector (aluminum foil, average thickness 20 μm, Ra 0.035 μm, manufactured by UACJ Corporation)
[0315] Support (S3): negative electrode current collector (copper foil, average thickness 10 μm, Ra 0.55 μm, manufactured by Nippon Denkai, Ltd.)
[0316] Support (S4): negative electrode current collector (copper foil, average thickness 12 μm, Ra 0.3 μm, manufactured by Furukawa Electric Co., Ltd.)
[0317] The Ra of the current collector mentioned above refers to the arithmetic mean roughness Ra of the surface on which the electrode material film is formed.
[0318] [Preparation of scrapers (B1) to (B2)]
[0319] Scraper (B1): Stainless steel scraper (with Figure 4 The scraper 20A shown in the figure has the same structure as the scraper 20A, and the scraper body 26A and the protrusion 28A are joined. The length of the scraper body 26A is 225mm, the width (length) of the central part 22 in the width direction is 211mm, the width (length) of the two ends 24 in the width direction is 7mm each, the protruding height of the two ends 24 in the width direction (the height of the protrusion 28A) is 0.3mm, the maximum height of the scraper 20A is 100mm, and the thickness of the scraper 20A is 10mm)
[0320] Scraper (B2): A laminated type scraper (with a PTFE layer and a stainless steel layer forming the contact portion with the electrode material) Figure 5 The scraper 20B shown in the figure has the same structure as the scraper 20B, and the scraper body 26B and the width limiting member 28B are joined. The length of the scraper body 26B (the width (length) of the central part 22 in the width direction): 180mm, the protruding height of the two ends 24 in the width direction: 0.3mm, the maximum height of the scraper 20B is 100mm, and the thickness of the scraper 20B is 30mm)
[0321] [Measurement of friction coefficient μ1 and friction coefficient μ2]
[0322] The friction coefficient μ1 and the friction coefficient μ2 were measured by the method described above.
[0323] Friction coefficient between scraper (B1) and positive electrode material (P1) μ1: 0.4
[0324] Friction coefficient μ1 between scraper (B1) and negative electrode material (P2): 0.18
[0325] Friction coefficient μ1 between scraper (B2) and positive electrode material (P1): 0.27
[0326] Friction coefficient between scraper (B2) and negative electrode material (P2) μ1: 0.2
[0327] Friction coefficient μ2 between positive electrode material (P1) and support (S1): 0.59
[0328] Friction coefficient μ2 between positive electrode material (P1) and support (S2): 0.35
[0329] The friction coefficient between the negative electrode material (P2) and the support (S3) is μ2: 0.4
[0330] The friction coefficient μ2 between the negative electrode material (P2) and the support (S4) is 0.25
[0331] Friction coefficient between scraper (B1) and positive electrode material (P3) μ1: 0.6
[0332] Friction coefficient between scraper (B1) and negative electrode material (P4) μ1: 0.3
[0333] Friction coefficient between scraper (B2) and positive electrode material (P3) μ1: 0.42
[0334] Friction coefficient between scraper (B2) and negative electrode material (P4) μ1: 0.225
[0335] Friction coefficient μ2 between positive electrode material (P3) and support (S1): 0.75
[0336] Friction coefficient μ2 between positive electrode material (P3) and support (S2): 0.52
[0337] The friction coefficient between the negative electrode material (P4) and the support (S3) is μ2: 0.6
[0338] The friction coefficient μ2 between the negative electrode material (P4) and the support (S4) is 0.34
[0339] <Example 1-1>
[0340] Use as Figure 1 and Figure 2 The device shown in the figure formed an electrode material film on the support. The support, the squeegee and the electrode material shown in Table 1 were used.
[0341] Specifically, the scraper 20 is arranged to maintain a constant distance C of 400 μm from the center of the width direction of the scraper 20 relative to the surface of the support 10 placed on the moving stage 70. In addition, at this time, the distance between both ends of the scraper 20 in the width direction and the surface of the support 10 is set to 100 μm.
[0342] Here, as the support 10, a support obtained by bonding a PET film having a heat-sealing layer composed of an ethylene-vinyl acetate copolymer (EVA) to the back surface of the support (1) by heat-sealing was used.
[0343] The electrode material 30 is supplied between the support 10 and the scraper 20 to form a reservoir, and then the support 10 is moved in the direction of the arrow by moving the stage 70, thereby limiting the thickness and width of the electrode material 30 by the scraper 20, as shown in FIG. Figure 2 As shown in FIG. 1 , an electrode material film 34 made of an electrode material 30 is formed on a support 10. The supply amount X of the electrode material 30 to the reservoir and the formation amount Y of the electrode material film are set to the values shown in Table 1.
[0344] When the electrode material 30 passes through the gap having the distance C, the scraper 20 is vibrated by the vibrator 60. The amplitude A of the vibrating scraper is 7 μm, and the period is 300 Hz.
[0345] Furthermore, the thickness B of the formed electrode material film 34 was 325 μm.
[0346] <Example 1-2 to Example 1-6>
[0347] As shown in Table 1, the types of the support, scraper and electrode material were appropriately changed, and as shown in Table 1, the distance C, the amplitude A of the scraper vibration, the supply amount X of the electrode material to the storage part and the formation amount Y of the electrode material film were appropriately changed. In addition, in the same manner as in Example 1-1, an electrode material film (a molded body for a sheet electrode for a positive electrode) with a thickness B of 325 μm was obtained.
[0348] <Example 2-1 to Example 2-6>
[0349] As shown in Table 2, the types of the support, scraper and electrode material were appropriately changed, and as shown in Table 2, the distance C, the amplitude A of the scraper vibration, the thickness B of the electrode material film, the supply amount X of the electrode material to the accumulation part and the formation amount Y of the electrode material film were appropriately changed. In addition, in the same manner as in Example 1-1, an electrode material film (a formed body for a sheet electrode for a negative electrode) with a thickness B of 335 μm was obtained.
[0350] <Comparative Example 1>
[0351] The electrode material film was formed on the support in the same manner as in Example 1-1 except that the scraper was not vibrated. In the case of Comparative Example 1, although an electrode material film with a thickness of 400 μm was obtained at the initial stage when the support 10 began to move in the direction of the arrow, a portion of the film was torn and a continuous film could not be formed. Therefore, the thickness B of the electrode material film could not be measured.
[0352] <Comparative Example 2>
[0353] The electrode material film was formed on the support in the same manner as in Example 2-1 except that the scraper was not vibrated. In the case of Comparative Example 2, although an electrode material film with a thickness of 400 μm was obtained at the initial stage when the support 10 began to move in the direction of the arrow, a portion of the film was torn afterwards, and a continuous film could not be formed. Therefore, the thickness B of the electrode material film could not be measured.
[0354] <Evaluation of thickness in-plane uniformity>
[0355] A contact displacement meter manufactured by Mitutoyo Corporation was placed on the platform, and the thickness of the sheet was measured for each collector foil, and the average thickness of the collector foil was subtracted to derive the thickness of the sheet electrode molded body obtained. In addition, the measurement positions were set to 3 positions in the width direction and 3 positions in the length direction for each sheet, for a total of 9 positions. In the case of Comparative Examples 1 and 2, only the positions where a continuous film was formed were measured.
[0356] The thickness variation rate was calculated based on the measured values. Max and minimum value X Min Average value X Ave The larger difference is found and the following formula 1 is used for calculation.
[0357] Formula 1: Thickness variation rate (%) = | maximum value X Max or minimum value X Min - Average value X Ave |÷Average valueX Ave ×100
[0358] Here, in Formula 1, the maximum value X Max It refers to the maximum value and minimum value X among the measured values (9 points). Min It refers to the minimum value among the measured values (9 points), the average value X Ave It refers to the arithmetic mean of the measured values (9-point components).
[0359] Based on the obtained value of the thickness variation rate, the in-plane uniformity of the thickness was evaluated according to the following criteria.
[0360] -standard-
[0361] A: The thickness variation rate value is 1% or less.
[0362] B: The thickness variation rate value exceeds 1% and is 2% or less.
[0363] C: The thickness variation rate value exceeds 2% and is 3% or less.
[0364] D: The thickness variation rate value exceeds 3% and is 5% or less.
[0365] E: The thickness variation value exceeds 5%.
[0366]
[0367] As can be seen from Tables 1 and 2, the electrode molded bodies obtained in Examples 1-1 to 1-6 and 2-1 to 2-6 have superior in-plane uniformity of thickness compared to the electrode molded bodies obtained in Comparative Examples 1 and 2.
[0368] Explanation of symbols
[0369] 10-support body, 20-scraper, 22-central part of the scraper in the width direction, 24-two end parts of the scraper in the width direction, 26A, 26B-main body of the scraper, 28A-convex part, 28B-width limiting component, 30-electrode material, 32-storage part of the electrode material, 34-electrode material film, 40-pressure shaft, 50-cylinder, 60-vibrator, 70-movable stage, C-distance.
[0370] The invention of Japanese Patent Application No. 2022-120972 filed on July 28, 2022 is incorporated herein by reference in its entirety. All documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if each document, patent application, and technical standard were specifically and individually described by reference.
Claims
1. A method for producing a sheet-shaped electrode molded body, comprising the step of forming an electrode material film on a support using an electrode material containing an electrode active substance and having a solid content concentration of 30% by volume or more, The electrode material film is formed in the following manner: a scraper having a shape in which both ends in the width direction protrude more than the central part in the width direction and in which the central part in the width direction vibrates is moved relative to the surface of a support body while maintaining a constant distance from the surface of the support body; the thickness of the electrode material supplied to the support body is limited by the gap between the surface of the support body and the central part in the width direction of the scraper, and the width is limited by both ends in the width direction of the scraper which protrude more than the central part in the width direction.
2. The method for producing a sheet-shaped electrode molded body according to claim 1, wherein: At least a portion of the electrode material supplied onto the support and before the thickness and width of the electrode material are restricted forms a reservoir in a region sandwiched between the support and the squeegee.
3. The method for producing a sheet-shaped electrode molded body according to claim 2, wherein: The electrode material is continuously or intermittently supplied to the reservoir.
4. The method for producing a sheet-shaped electrode molded body according to claim 3, wherein: The ratio X:Y of the amount X of the electrode material supplied to the liquid reservoir and the amount Y of the electrode material film formed on the support is 1:0.1 to 1:1 on a mass basis.
5. The method for producing a sheet-shaped electrode molded body according to claim 1 or 2, wherein: The friction coefficient μ1 of the contact portion of the scraper contacting the electrode material and the electrode material is smaller than the friction coefficient μ2 of the electrode material and the support.
6. The method for producing a sheet-shaped electrode molded body according to claim 1 or 2, wherein: The ratio A:B of the amplitude A of the central portion in the width direction of the vibrating scraper and the thickness B of the electrode material film formed on the support is 1:10 to 1:200.
Citation Information
Patent Citations
Method of forming through electrode of circuit board
JP2011071153A
Electrochemical cell having a semi-solid electrode and method for manufacturing the same
JP2017533548A
Virtual aviation service system
JP2022120972A